Discrete Carleman estimates and three balls inequalities - Fernández-Bertolin, Aingeru; Roncal, Luz; Rüland, Angkana; Stan, Diana (Arxiv, 2020)
We prove logarithmic convexity estimates and three balls inequalities for discrete magnetic Schr\"odinger operators. These quantitatively connect the discrete setting in which the unique continuation property fails and the continuum setting in which the unique continuation property is known to hold under suitable regularity assumptions. As a key auxiliary result which might be of independent interest we present a Carleman estimate for these discrete operators.
Last revised 26 Jan 2021 (v3)
Gesehen am 27.05.2021